Ulnar nerve entrapment neuropathy at the elbow: relationship between the electrophysiological findings and neuropathic pain - HALAC, Gulistan; Topaloglu, Pinar; DEMIR, Saliha; CIKRIKCIOGLU, Mehmet Ali; KARADELI, Hasan Huseyin; OZCAN, Muhammet Emin; Asil, TALİP; ASİL, TALIP (My University, 2015)
[Purpose] Ulnar nerve neuropathies are the second most commonly seen entrapment neuropathies of the upper extremities after carpal tunnel syndrome. In this study, we aimed to evaluate pain among ulnar neuropathy patients by the Leeds assessment of neuropathic symptoms and signs pain scale and determine if it correlated with the severity of electrophysiologicalfindings. [Subjects and Methods] We studied 34 patients with clinical and electrophysiological ulnar nerve neuropathies at the elbow. After diagnosis of ulnar neuropathy at the elbow, all patients underwent the Turkish version of the Leeds assessment of neuropathic symptoms and signs pain scale. [Results] The ulnar entrapment neuropathy at the elbow was classified as class-2, class-3, class-4, and class-5 (Padua Distal Ulnar Neuropathy classification) for 15, 14, 4, and 1 patient, respectively. No patient included in class-1 was detected. According to Leeds assessment of neuropathic symptoms and signs pain scale, 24 patients scored under 12 points. The number of patients who achieved more than 12 points was 10. Groups were compared by using the χ(2) test, and no difference was detected. There was no correlation between the Leeds assessment of neuropathic symptoms and signs pain scale and electromyographic findings. [Conclusion] We found that the severity of electrophysiologic findings of ulnar nerve entrapment at the elbow did not differ between neuropathic and non-neuropathic groups as assessed by the Leeds assessment of neuropathic symptoms and signs pain scale.